Acute hepatitis A virus infection in patients hospitalised at the Department of Infectious Diseases, Medical University of Lublin (Eastern Poland) in the years 2009-2015 - Krzowska-Firych, Joanna M.; Lucas, Georgia; Lucas, Christiana; Łukowski, Marcin; Maciak, Dawid; Tomasiewicz, Krzysztof (Clinical and Experimental Hepatology, 2016)
The aim of our study was to analyse all medical records from the years 2009-2015 for adult patients with acute hepatitis A virus (HAV) infection who were hospitalised at the Department of Infectious Diseases, Medical University of Lublin (Eastern Poland). During this 7-year study, there were only 5 hospitalised patients with confirmed HAV infection. In the study group 4 out of 5 patients had travelled to HAV-endemic areas (Egypt, Ukraine), and 3 of the hepatitis A cases were imported from Egypt. Our data indicate that during the past 7-year period most HAV patients hospitalised at the Department of Infectious Diseases in Lublin were due to travel.